2018
DOI: 10.1140/epjp/i2018-12099-5
|View full text |Cite
|
Sign up to set email alerts
|

Exact energy spectrum of the generalized Dirac oscillator in an electric field

Abstract: We study generalized (1+1)-dimensional Dirac oscillator in nonuniform electric field. It is shown that in the case of specially chosen electric field the eigenvalue equation can be casted in the form of supersymmetric quantum mechanics. It gives a possibility to find exact solution for the energy spectrum of the generalized Dirac oscillator in nonuniform electric field. Explicit examples of exact solutions are presented. We show that sufficiently large electric field destroys the bounded eigenstates.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 15 publications
(18 reference statements)
1
14
0
Order By: Relevance
“…and the energies E ,s py,n of our system are In the particular case, when p y = 0, this result agrees exactly with that of Ref. 43.…”
Section: Exact Calculation For the Green's Functionsupporting
confidence: 92%
See 1 more Smart Citation
“…and the energies E ,s py,n of our system are In the particular case, when p y = 0, this result agrees exactly with that of Ref. 43.…”
Section: Exact Calculation For the Green's Functionsupporting
confidence: 92%
“…In this regard, it is worth mentioning that the general Dirac oscillator subjected to a non-uniform electric field was studied in Ref. 43. It was found, in this reference, that in the case of specially chosen electric field, the eigenvalue equation can be resolved exactly.…”
Section: Introductionmentioning
confidence: 98%
“…Such oscillators, initially introduced as systems linear in momentum and coordinate variables [29], are closely related to Dirac models coupled to magnetic fields. Applications include experimental realizations of Dirac oscillators [17], their coupling to electric fields [23], and within a rotating reference frame [39]. Interestingly, it has been shown that in (2 + 1) dimensions the Dirac oscillator is equivalent to a spin 1/2 particle in a magnetic field [11].…”
Section: Introductionmentioning
confidence: 99%
“…After then, the context of SUSY QM was first studied by Witten [17] and Cooper and Freedman [18]. This theory, which still attracts much attention today, has also application in optics [19] and biophysics [20]; it has a very important place in both relativistic [21] and nonrelativistic quantum mechanics [22,23]. This work points the dynamics of a massless fermion out when it is under the influence of a magnetic field.…”
Section: Introductionmentioning
confidence: 99%